Negative Labeling towards Teachers as Expression of Violence in Modern Literature - Manurung, Rosida Tiurma; Suganda, Dadang; Cristiana, Davidescu (EDUCARE, 2014)
ABSTRACT: Previous to 1960, the literatures recognized teachers as highly respected figures. Upon seeing a teacher from far away, a student would hurriedly run to reach him/her and would lead his/her bike. It was considered an honor to help teachers in one way or another. Time and time in the past literature, teachers are labeled in such ways that the students would kiss their teachersâ hands to show them respect. The students would not hesitate to give their selves away to help cut their teachersâ grass. However, it is no longer the case in todayâ literatures. The literatures repeatedly make fun of teachers, as well harassing and paralyzing them. It is ironical. Teachers have lost their positive label and are labeled negatively as the product of indecent behavior from the part of the students. Schools are becoming the fields for channeling violent attitude and behaviors to ruin the good image of a teacher. In this work, teachers labeling in the past and todayâ literature are compared. Literatures from 1960s and 2000s become the sources of data. Language expression is analyzed with the help of Critical Discourse Analysis using the method of contrasted descriptive and analysis, while data are collected by the technique of library study and interviews. It is expected that the result of the research help put the teachersâ label (already fading away, corrupted, and falling onto pieces) on its early respected place again. Teachers with positive image are always needed and cannot be compromised. With the positive label of teachers, the process of studying and teaching can be performed more conducive, effective, interactive, and optimum. Positive labeling of teachers need to be started in today literature. Poets and authors have the central role to give appreciation for the teachers.KEY WORDS: Teachers labeling, violent expression, 1960sâ literature, todayâ literature, contrasted analysis, and critical discourse analysis.Â Â Â Â About the Authors: Rosida Tiurma Manurung is a Ph.D. Student at the Postgraduate Program of Literature Science, Majoring in Linguistic UNPAD (Padjadjaran University) in Bandung, West Java, Indonesia; and Prof. Dr. Dadang Suganda and Prof. Dr. Davidescu Cristiana are the Lecturers at the Faculty of Humanities UNPAD Bandung. Corresponding author is: rosidatm@gmail.comHow to cite this article? Manurung, Rosida Tiurma, Dadang Suganda & Davidescu Cristiana. (2014). âNegative Labeling towards Teachers as Expression of Violence in Modern Literatureâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.161-168. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 26, 2013); Revised (January 29, 2014); and Published (February 17, 2014).Â Â